Photovoltaic and thermoelectric indirect coupling for maximum solar energy exploitation. (15th March 2017) - Hajji, M.; Labrim, H.; Benaissa, M.; Laazizi, A.; Ez-Zahraouy, H.; Ntsoenzok, E.; Meot, J.; Benyoussef, A.
Highlights: New Hybrid system coupling photovoltaic and thermoelectric are studied. Thermal transfer Method. The effect of coupling types which are direct and indirect are examined. The Heat Transfer is modeled in Hybrid system. The indirect coupling significantly improves the overall efficiency. Abstract: Advanced photovoltaic devices with a high performance/cost ratio is a major concern nowadays. In the present study, we investigate the energetic efficiency of a new concept based on an indirect (instead of direct) photovoltaic and thermoelectric coupling. Using state-of-the-art thermal transfer calculations, we have shown that such an indirect coupling is an interesting alternative to maximize solar energy exploitation. In our model, a concentrator is placed between photovoltaic and thermoelectric systems without any physical contact of the three components. Our major finding showed that the indirect coupling significantly improve the overall efficiency which is very promising for future photovoltaic developments.